Assessing Arabic Speaking Skills: A Critical Study for Implementation of Final Examination in Indonesia - Widiya Yul; Riko Andrian; Ahmad Musthofa; Jihan Fitri Rozianie (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
Assessment is one of the basic processes in the educational process after determining goals and teaching students. The national school final examination, in Indonesia called UAMBN, is one of the programs for conducting Arabic language tests, and focuses on assessing four skills of students. In fact, speaking skills test is not in the program. The purpose of this research is to criticize the lack of implementation of speaking skills assessment at UAMBN. Researcher used a critical methodology to analyze the data by configuration of four analytically distinguished but intertwined dimensions: (1) critical understanding and in-depth examination, (2) critical explanation and comparative generalization, (3) open discourse and transformative redefinition or action, and (4) reflexive–dialectic argumentation. The results of the study are the absence of an Arabic speaking skill test in the national madrasah final exam/UAMBN cannot be tolerated. Distributing the assessment process in national school final exams/USBN is not the right solution. UAMBN should still hold Arabic speaking skills tests in special sessions. The solution in the form of an assessment implementation design is available in this study. Further research related to the application of this design is highly recommended to improve the quality of learning Arabic speaking skills.